Framing the text: understanding emotional barriers to academic reading - Kimberley, Emma; Thursby, Mark (Journal of University Teaching and Learning Practice, 2020)
When students arrive at university there is an expectation that they come already equipped with the skills they need to read academic texts. In contrast, many students have low confidence in their ability to read challenging texts, often experiencing this as a barrier to engaging with academic practices. Recent research has identified the importance of affect in the university context, exploring the impact of emotions around academic practices such as critical thinking and interpreting feedback, but has not looked specifically at reading as one such key practice. This paper draws on this research and reads it alongside data gathered from questionnaires and focus groups conducted with one group of first-year undergraduates. We found that students have a complex relationship with reading for academic study, and that many experience significant negative affects and self-perceptions in relation to their academic reading tasks. We explore some of these encounters, engaging the student voice and using affect theory to unpack some first experiences of reading in higher education.